Students’ and Lecturers’ Perceptions toward Interactive Multimedia in Teaching Academic Writing - Oktarina, Santi; Indrawati, Sri; Slamet, Adeng (Journal of Education Reseach and Evaluation, 2022)
Writing ability is expected to be achieved by all students because it dramatically affects academic achievement. However, some students have poor writing skills. The purpose of this study was to analyze data on student and lecturer perceptions of the use of media/multimedia in academic writing for Indonesian language courses. This type of research is development. Data collection methods in analyzing objective situations are questionnaires, interviews, and focus group discussions (FGD). The instruments used in collecting data are questionnaires and interview sheets. The technique used to analyze the data is descriptive qualitative and quantitative analysis. The research results are that students and lecturers feel that teaching and learning academic writing in Indonesian language courses do not apply interactive multimedia. Most of the teaching sessions use PowerPoint presentation slides and course books. Furthermore, they hope to use interactive multimedia in academic learning so that the sessions will be more exciting and engaging, not dull, use animations and videos, and can be accessed anytime, anywhere.